2019
DOI: 10.1111/jam.14539
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon source complexity on porosity, water retention and extracellular matrix composition ofNeurospora discretabiofilms

Abstract: Aims To evaluate carbon source complexity as a process lever to impact the microstructure, chemical composition and water retention capacity of biofilms produced by Neurospora discreta. Methods and Results Biofilms were produced by nonpathogenic fungus N. discreta, using sucrose, cellulose or lignin as carbon source. The increase in complexity of carbon source from sucrose to lignin resulted in decreased water retention values (WRV) and wet weights of harvested biofilms. Confocal laser scanning microscopy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Being able to greatly affect cell migration, oxygen regulation and nutrient exchange, porosity is a key parameter that should be considered during a scaffold design 61 . Usually, in tissue engineering applications, average pore size is measured by the post-processing of SEM micrographs, while total porosity can be calculated separately by liquid displacement method, typically employing ethanol 47 , 62 , 63 . In this work, both total porosity and size pore distribution were inferred from mercury intrusion porosimetry (MIP, see Experimental Methods section) analysis, to ensure that the whole range of sizes presented by these natural, highly-variable materials, could be included (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being able to greatly affect cell migration, oxygen regulation and nutrient exchange, porosity is a key parameter that should be considered during a scaffold design 61 . Usually, in tissue engineering applications, average pore size is measured by the post-processing of SEM micrographs, while total porosity can be calculated separately by liquid displacement method, typically employing ethanol 47 , 62 , 63 . In this work, both total porosity and size pore distribution were inferred from mercury intrusion porosimetry (MIP, see Experimental Methods section) analysis, to ensure that the whole range of sizes presented by these natural, highly-variable materials, could be included (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 a). Furthermore, in our previous works, it has been reported that morphology, chemical composition, hydrodynamics and mechanical properties of mycelia can be finely tuned by changing both the fungal strain and their growth substrate 45 47 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Ahmed, Narayanan, and Veni (2019) evaluated the relationship between Neurospora discreta biofilm and carbon sources. The authors focused on the microstructure, chemical composition, water retention capacity, porosity, and wet weight of the biofilm and carbon sources.…”
Section: Impact Of Nutrients Nanomaterial Toxicity and Other Factorsmentioning
confidence: 99%